Fostering Engagement and Understanding: The Impact of Kolb’s Experiential Learning Theory on Teaching Theory of Machines - Beldar, Pankaj; Galande, Vishal; Panchbhai, Mangesh; Kavale, Prashant (Journal of Engineering Education Transformations, 2025)
Despite being an essential subject in mechanical engineering education, the Theory of Machines (TOM) frequently presents substantial difficulties for students because of its mathematical rigor and abstract concepts. Learners are often not adequately engaged by traditional teaching approaches, which results in a superficial comprehension of basic concepts. This study investigates how to improve student engagement and comprehension in TOM courses by implementing Kolb's Experiential Learning Theory (KELT) as a teaching paradigm. This study intends to promote greater connections between theoretical knowledge and real-world application by incorporating experiential learning activities like practical projects, simulations, and group learning opportunities. The study assesses how experiential learning affects students' drive, critical thinking, and recall of TOM ideas using a mixed-methods methodology. According to the results, applying Kolb's ELT fosters a more dynamic and interesting learning environment in addition to enhancing comprehension of difficult subjects. This case report demonstrates how methods of hands-on education have the power to revolutionize Theory of Machines instruction and ultimately equip engineering students for problems they may face in the real world.